The Use of Error Analysis to Assess EFL Learners' Writing Performance The Case of Third Year Pupils at Abdaoui Middle School ( Ain el Hadjel / M'sila) - Djawhara DJOUADI .Smahan OUBAH, Imane CHERIET (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
ABSTRACT Today, Error analysis is gaining popularity in second and foreign language classrooms. Many researchers affirm that the use of error analysis can be profitable in having a deep understanding of language learners' errors especially of their writing ones. Therefore, the present work does not only aim at exploring teachers’ perceptions and their current practices of written feedback provision in middle school EFL classes but also to examine whether error analysis can effectively be used by middle school teachers as a tool to assess learners’ writing performance. To achieve these objectives, a triangulation of research tools were used. The tools are; an online questionnaire for middle school teachers, a writing test to middle school learners, an evaluation grid for raters based on Corder’s model of error analysis and an evaluation model grid for raters to test the usefulness and validity of the suggested model. Hence, thirty written compositions were analyzed by five Algerian middle school teachers using the suggested model. The sample of this study was 35 middle school teachers and 30 middle school pupils. The findings revealed that assessing writing is not an easy task and that teachers are in need to use evaluation techniques that help them to cope with the challenges they face when assessing their pupils’ productions. It was also highlighted that error analysis can be a useful tool to identify and examine pupils’ errors and thus address them, yet better error analysis-based models can be designed to facilitate teachers writing assessment. This study calls for further research in this area and concludes with a set of pedagogical implications including the importance of feedback and remedial work in writing classes to improve the writing skill among EFL middle school pupils
Keywords: Keywords: Error.EFL Learners.' Writing Performance